Zinc Electrode Morphology Evolution in High Energy Density Nickel-Zinc Batteries - Payer, Gizem; Ebil, Özgenç; Ebil, Özgenç (Hindawi Publishing Corporation, 2016)
Prismatic Nickel-Zinc (NiZn) batteries with energy densities higher than 100 Wh kg-1 were prepared using Zn electrodes with different initial morphologies. The effect of initial morphology of zinc electrode on battery capacity was investigated. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) reveal that initial morphology of zinc electrode changes drastically after a few charge/discharge cycles regardless of initial ZnO powder used. ZnO electrodes prepared using ZnO powders synthesized from ZnCl2 and Zn(NO3)2 lead to average battery energy densities ranging between 92 Wh kg-1 and 109 Wh kg-1 while using conventional ZnO powder leads to a higher energy density, 118 Wh kg-1. Average discharge capacities of zinc electrodes vary between 270 and 345 mA g-1, much lower than reported values for nano ZnO powders in literature. Higher electrode surface area or higher electrode discharge capacity does not necessarily translate to higher battery energy density.
Keywords: Electric batteries; High energy densities; Zinc; Nickel; Initial morphology